Modification of Morphology of PS/LDPE/ Mg(OH)(2) and PS/LDPE/SBS/Mg(OH)(2) Polymer Composites by Supercritical CO2 - (:unkn) unknown (PRINTS PUBLICATIONS PVT LTD, 2011)
In this paper, we explore a supercritical carbon dioxide processing method that utilizes CO2 to disperse Mg(OH)(2). The structure and properties of the composites are characterized using a scanning electron microscopy (SEM), Differential scanning calorimeter (DSC) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, PS/LDPE/SBS/Mg(OH)(2) polymer composites were subjected to examinations to obtain their tensile strengths, elasticity modulus, % elongation, lzod impact strength, hardness, Heat deflection temperature (HDT),Vicat softening point and Melt flow index (MFI).
Keywords: Polystyrene; polyethylene; styrene butadiene styrene; supercritical carbon dioxide; polymer composites; CARBON-DIOXIDE; CELL-GROWTH; NUCLEATION; GENERATION; PRESSURE; FOAM